Key Audit Matters, Audit Quality and Audit Fees: Evidence from China - Yang, Yingkui (2022)
This paper examines the economic consequences of the implementation of the new auditing reporting standards from the standpoints of audit quality and audit fees in the context of the new auditing standards' exogenous event. Much of the existing research has focused on the empirical study of key audit matters on audit quality, but there is a lack of research on the relationship between key audit matters, audit quality and audit fees. Therefore, this paper selects China listed companies in 2015-2016 as the research sample and empirically tests the three hypotheses on key audit matters, audit quality and audit fees based on theoretical analysis. In the specific design of the empirical study, the absolute value of manipulative accrued profits was selected as an indicator of audit quality, and the results of the logarithm of audit fees and the disclosure of key audit matters were taken as the main explanatory and explanatory variables, together with control variables, as the empirical model of the paper. The Propensity Score Matching PSM method and Difference in Differences DID regression were used to analyse and regression test the model, and finally the empirical results were tested for robustness. The main findings of this paper are as follows: Firstly, A-share companies saw a significant decrease in accrual of earning management following the implementation of the key audit matter standard when compared to control group companies that did not implement the key audit matter standard. Secondly, audit fees have risen significantly since the key audit matter standard was implemented. Thirdly, an increase in audit fees leads to higher audit quality, implying that higher audit fees lead to greater care and dedication in the auditor's practice, which leads to higher audit quality.